Me & Mama - Cabrera, Cozbi A. (2020)
For a little girl on a rainy day, the best place to be is with Mama
"A Denene Millner Book."
Ages 4-8
Keywords: Mothers and daughters -- Juvenile fiction; Children's stories; Picture books; Fiction; Juvenile works